1978
DOI: 10.1111/j.1365-2621.1978.tb02303.x
|View full text |Cite
|
Sign up to set email alerts
|

Soymilk: A Comparison of Processing Methods on Yields and Composition

Abstract: Soymilk was produced by (A) heating of intact soybeans after soaking but before disruption, (B) heating of soaked soybeans to 80°C during disruption, and (C) disruption of soaked soybeans with no prior heating. The results show that process A has low yields of solids and low recoveries of protein in comparison with processes B and C. Heating of soybeans preceding disruption seems to keep protein bodies intact when soybean cells are disrupted. Homogenization will redisperse protein bodies that have been fixed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
50
2
2

Year Published

1982
1982
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 7 publications
9
50
2
2
Order By: Relevance
“…Three different methods described by Johnson and Snyder (1978) were used in soymilk production. The methods include Illinois, Cornel, and Traditional Chinese.…”
Section: Preparation Of Soymilkmentioning
confidence: 99%
See 1 more Smart Citation
“…Three different methods described by Johnson and Snyder (1978) were used in soymilk production. The methods include Illinois, Cornel, and Traditional Chinese.…”
Section: Preparation Of Soymilkmentioning
confidence: 99%
“…The most common method of soymilk production is the Traditional Oriental method in which soybean is soaked overnight, crushed wet and sieved to get soymilk. Johnson and Snyder (1978) described two other methods of processing termed Illinois and Cornell methods. These methods were aimed at improving the acceptability of soymilk in terms of odour, and flavour.…”
mentioning
confidence: 99%
“…protein extraction (Golbitz 1995;. In the Illinois method, where soybeans are blanched for 30 minutes, Johnson and Snyder (1978) showed that the initial blanching step would heat fixed the protein bodies in the soybeans and make it insoluble even after the grinding step. If the soybeans are ground with hot water, such as in the Cornell method, the protein fixation does not occur and better extraction can be obtain.…”
Section: (Lox)mentioning
confidence: 99%
“…149 and 150). Johnson and Snyder (1978) found that when soybeans were heated prior to cellular disruption, intact protein bodies (2.0 to 10.0^m in diameter) could be observed. However, intact protein bodies were not observed in slurries of unheated soybeans.…”
Section: Membranementioning
confidence: 99%
“…In a study on soymilk preparation, Johnson and Snyder (1978), found that typical protein bodies (2 to 10in diameter) were present only in heated soy slurries/ whereas unheated preparations appeared to contain much smaller particles. Johnson claimed that protein bodies appeared to be "fixed" in some manner by the heat treatment prior to grinding and suggested that they were possibly more resistant to disruption upon grinding than protein bodies in unheated preparations.…”
Section: Relationship Of Processing and Soybean Ultrastructurementioning
confidence: 99%